Effect of Feeding Diets Supplemented with an Antibiotic or Probiotic on the Carcass Characteristics and Economics of Commercial Broiler Chicken - Patel, Hard V; Rajpura, Rais M; Paleja, Haidaruliman I; Patel, Atul B; Bhagora, Nikesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was aimed to evaluate the growth-promoting activity of probiotics and antibiotics in broilers. A total of 540 straight run day-old commercial broiler chicks (Vencobb-430) were randomly assigned to three treatment groups. Each treatment comprised of six replicates, with 30 chicks in each, resulting in 180 chicks per treatment. Treatment Group 1 served as the control group, while Group T2 was supplemented with antibiotics (Enramycin hydrochloride 8 % @ 100 g/ton of feed from 0-42 days; and Neomycin sulphate + Doxycycline from 2nd to 5th day, Sulphadiazine + Trimethoprim from 16th to 19th day; and Enrofloxacin from 30th to 33rd day in water each combination @ 10 mg/kg b.wt.), and Group T3 received probiotics (1 billion cfu/g of strains) in feed from 0-42 days and in water from 2nd to 5th day, 16th to 19th day and 30th to 33rd. To assess growth-promoting activity, parameters such as carcass characteristics, livability, GI tract and internal organ morphometry and economics as return over feed cost were recorded. The results indicated that at the end of 42nd days, no significant differences were observed in any of the parameters studied among the three experimental groups, although the antibiotic-supplemented group exhibited numerical improvements compared to the other groups. At the end of experiment probiotic supplemented group was found to have some improvement in length of colo-rectum compared to other group. The incorporation of probiotics led to numerical improvements in ROFC compared to the control group. The observed improvements in the probiotic and antibiotic-supplemented groups may be attributed to their gut microflora-stabilizing properties, resulting in enhanced gut absorption of nutrients.